Evaluation of diets based on Brachiaria grass with different levels of byproducts from the biodiesel industry using in vitro gas production degradability - Freire, Juliana Marques; Silva, Aderbal Marcos de Azevedo; Carneiro, Heloisa; Pereira Filho, José Morais; Moura, Daiane Caroline de; Pinheiro, Jovanna Karine (Medicina Veterinária, 2020)
This study was performed to evaluate the production of gas and volatile fatty acids in diets containing byproducts from the national biodiesel industry (castor bean, canola, forage turnip, and black sunflower) in four levels (0, 30, 50 and 70%), through the use of a semi-automated in vitro technique. The inoculum for in vitro incubation was obtained from three fistulated Holstein cows. This was a 4 x 4 factorial completely randomized experimental design consisting of four levels of four byproducts. The byproduct of forage turnip was the ingredient of greatest potential for producing acetate, propionate, and butyrate. The increased production of carbon dioxide and methane in relation to the degraded dry matter was obtained using the byproduct of canola (P<0.05). The byproduct of castor bean resulted in the lowest potential for producing acetate, propionate, and butyrate; and among the evaluated byproducts it can be considered the one with the least impact to the environment without damage to ruminal fermentation.